Changes in depressive symptoms and cognitive impairment in older long-stay nursing home residents in the USA: a latent transition analysis. (3rd October 2021) - Yuan, Yiyang; Lapane, Kate L.; Rothschild, Anthony J.; Ulbricht, Christine M.
Abstract: Objectives: To longitudinally examine the latent statuses of depressive symptoms and their association with cognitive impairment in older U.S. nursing home (NH) residents. Method: Using Minimum Data Set 3.0, newly-admitted, long-stay, older NH residents with depression in 2014 were identified ( n  = 88, 532). Depressive symptoms (Patient Health Questionnaire-9) and cognitive impairment (Brief Interview of Mental Status) were measured at admission and 90 days. Latent transition analysis was used to examine the prevalence of and the transition between latent statuses of depressive symptoms from admission to 90 days, and the association of cognitive impairment with the statuses at admission. Results: Four latent statuses of depressive symptoms were identified: ' Multiple Symptoms ' (prevalence at admission: 17.3%; 90 days: 13.6%), ' Depressed mood ' (20.0%; 19.5%), ' Fatigue ' (27.4%; 25.7%), and ' Minimal Symptoms ' (35.3%; 41.2%). Most residents remained in the same status from admission to 90 days. Compared to residents who were cognitively intact, those with moderate impairment were more likely to be in ' Multiple Symptoms ' and ' Fatigue ' statuses; those with severe impairment had lower odds of belonging to ' Multiple Symptoms ', ' Depressed Mood ', and ' Fatigue ' statuses. Conclusion: By addressing the longitudinal changes in the heterogeneous depressive symptoms and the role of cognitive impairment, findings have implications for depression management in older NH residents.